Assessing Information Security Resilience Using ISO/IEC 27001 and KAMI Index 5.0 - Fitri Safnita; Putri Ramdani; Maisan Dewi Puspa Khairani; Eka Ramadhani Putra (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2026)
Digital transformation in the government sector has increased the use of information technology in delivering public services. This condition requires government organizations to ensure adequate information security to protect data and systems from various cyber threats. This study aims to assess the level of information security resilience at the Communication and Informatics Office of Padang City in supporting digital transformation by referring to the ISO/IEC 27001 standard and using the KAMI Index 5.0 evaluation instrument. The research employed a descriptive approach with data collection techniques including observation, interviews, and document analysis in the KAMI Index assessment process. The results show that the level of compliance with the information security framework achieved a score of 518, indicating that the organization has met the basic framework for implementing information security based on the ISO/IEC 27001 standard. However, the implementation maturity level remains at Level II, indicating that several information security management processes have been implemented but are not yet fully documented and optimally managed. Therefore, improvement recommendations are proposed to enhance the maturity level, comprising specific recommendations across seven areas: information security governance (5), risk management (14), security framework (5), asset management (13), technology and security (6), personal data protection (11), and supplementary (6). These recommendations are expected to serve as a foundation to improve information security management effectiveness, thereby supporting the sustainability of local government digital services.